Transition From Parenteral to Enteral Nutrition and Postnatal Growth in Very Preterm Infants During Their First 28 Days of Life - Wang, Na; Zhang, Jia; Wang, Bo; Yu, Zhangbin; Han, Shuping; Wang, Huaiyan; Chen, Rongrong; Gu, Li; Gao, Yan; Hou, Weiwei; Lu, Xingxing (Frontiers in Pediatrics, 2022)
Background Nutrition practices for preterm infants during the first few weeks of life can be divided into three phases: the parenteral nutrition (PN), enteral nutrition (EN), and transition (TN) phases; the TN phase includes both PN and EN. Our purpose was to analyze nutrition practices for very preterm infants during the TN phase and their association with the infants' growth during the first 28 days of life. Methods Data from 268 very preterm infants <32 weeks old from six neonatal intensive care units were analyzed retrospectively. The TN phase was defined as enteral feedings of 30-120 ml/kg/d. Postnatal growth failure (PGF) was defined as a 28-day growth velocity <15 g/kg/d. Differences in protein and energy intake between the PGF and non-PGF groups during the TN phase were calculated, and risk factors for PGF were identified using multivariate regression analysis. Results The total protein (parenteral + enteral) intake during the TN was 3.16 (2.89, 3.47) g/kg/d, which gradually decreased as the enteral feeding volume increased in the TN phase. The total energy (parenteral + enteral) intake during the TN phase was 115.72 (106.98, 122.60) kcal/kg/d. The PGF group had a lower total protein intake (parenteral + enteral) than the non-PGF group had [3.09 (2.85, 3.38) g/kg/d vs. 3.27 (3.06, 3.57) g/kg/d, P = 0.007, respectively]. No significant difference was found in energy intake during the TN phase. The variables associated with PGF included a lower total protein (parenteral + enteral) intake, a smaller day of age at the end of the TN phase, and a higher birth weight z-score. Conclusion Increasing the total protein intake (parenteral + enteral) during the TN could reduce the incidence of PGF.